2006
DOI: 10.1542/peds.2006-1226
|View full text |Cite
|
Sign up to set email alerts
|

Public Parks and Physical Activity Among Adolescent Girls

Abstract: Background-Proximity to routine destinations is an important correlate of physical activity. We examined the association between distance from school and physical activity in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
280
5
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(299 citation statements)
references
References 23 publications
10
280
5
4
Order By: Relevance
“…This finding was shared by other studies (Aniza and Fairuz, 2009;Cohen et al, 2006;Ries et al, 2008) that suggested that proximity might influence physical activity. It appears that adolescents are thought to have more constrained mobility than an adult because they do not possess transportation at this age (Cohen et al, 2006). Therefore, it is essential to have a neighbourhood park that is located close to home to increase the opportunities for adolescents to engage in physical activity.…”
Section: Proximitysupporting
confidence: 83%
See 1 more Smart Citation
“…This finding was shared by other studies (Aniza and Fairuz, 2009;Cohen et al, 2006;Ries et al, 2008) that suggested that proximity might influence physical activity. It appears that adolescents are thought to have more constrained mobility than an adult because they do not possess transportation at this age (Cohen et al, 2006). Therefore, it is essential to have a neighbourhood park that is located close to home to increase the opportunities for adolescents to engage in physical activity.…”
Section: Proximitysupporting
confidence: 83%
“…People would like to engage in physical activity in recreational areas, such as neighbourhood parks, public parks, sports complexes and community parks (Cohen et al, 2006;Floyd et al, 2011). Thus, it is essential to create venues that are conducive to physical activity in residential areas to encourage physical activity (Shukur, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown, for instance, that the number of parks within an 800-m distance from home is associated with adolescent girls' non-school physical activity. 21 It has also been found that adolescents who have a park within a walking distance are likely to do physical activity regularly. 22 However, the spatial data available to us for our study did not allow the proximity to students' residential addresses of parks and other outdoor recreation facilities to be examined, given the district-based recruitment method that was used.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the facility-specific analyses, the number of parks was associated with the number of blocks of VPA. In the combined facility analysis, parks were associated with total METs in white girls only.…”
Section: Discussionmentioning
confidence: 99%